國中普通班身心障礙學生親子互動、自我概念與學校適應之關係研究 Relationships Between the Parent-Child Interaction, Self-Concept, and School Adjustment of Junior High School Students With Disabilities - 黃瓊儀 Chiung-Yi Huang; 游錦雲 Ching-Yun Yu; 吳怡慧 I-Hwey Wu (National Taiwan Normal University, 2018)
本研究主要目的在探討國中普通班七年級身心障礙學生親子互動及自我概念對多面向學校適應（師生關係、同儕關係、活動參與、學校氣氛、學業成就、合宜行為）之影響。本研究使用特殊教育長期追蹤資料庫所蒐集的1,482 位身心障礙學生資料，透過結構方程模式來檢定親子互動對自我概念與學校適應的直接效果、自我概念對學校適應的直接效果，以及探討親子互動透過自我概念影響學校適應之間接效果。研究結果顯示：親子互動對自我概念、師生關係、活動參與、學校氣氛、學業成就、合宜行為均有正向顯著影響，但親子互動對同儕關係之影響未達顯著；自我概念對師生關係、同儕關係、活動參與及學校氣氛有正向顯著影響，但自我概念對學業成就、合宜行為之影響未達顯著；親子互動透過自我概念對師生關 係、同儕關係、活動參與、學校氣氛有正向顯著的間接效果。最後針對研究結果，提出相關討論與建議。 This study explored the relationships between the parent-child interaction, self-concept, and school adjustment of junior high school students with disabilities. A sample of 1,482 junior high school students with disabilities were selected from the surveys of the Special Needs Education Longitudinal Study (SNELS). On the basis of empirical and theoretical research, a causal model of the parent-child interaction, self-concept, and multiple dimensions of school adjustment of junior high school students with disabilities (teacher-student relationship, peer relationship, activity participation, school climate, academic achievement, and appropriate behavior) was formed and validated using structural equation modeling. The mediation effect of the self-concept variable was evaluated. The findings demonstrated that parent-child interaction had no significant effect on peer relationship but had positive and significant effects on self-concept, teacher-student relationship, activity participation, school climate, academic achievement, and appropriate behavior. Self-concept had positive effects on the teacher-student relationship, peer relationship, activity participation, and school climate but did not have positive effects on academic achievement or appropriate behaviors. Moreover, self-concept played a mediation role between the parent-child interaction and several dimensions of school adjustment. Parent-child interaction indirectly influenced the teacher-student relationship, peer relationship, activity participation, and school climate through self-concept. This study also proposed some relevant suggestions on the basis of the findings.